Implementasi Akad Mudharabah dan Murabahah: Studi pada Bank Syariah Indonesia Cabang Jambi - Poniran Poniran; Amrizal Amrizal (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2025)
This study aims to examine the implementation of mudharabah and murabahah financing contracts at Bank Syariah Indonesia (Jambi Branch). The research employs a qualitative approach using a case study design. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing or verification. Data validity was ensured through source triangulation, data collection triangulation, and time triangulation. The results show that the implementation of murabahah contracts in working capital financing at Bank Syariah Indonesia may involve modifications through the addition of collateral. Murabahah financing is considered more favorable than other financing schemes because it can be used for both KUR and consumptive financing, with repayments made through an installment system. Meanwhile, mudharabah financing in the MSME sector has experienced a decline due to the impact of the Covid-19 pandemic.